The word Aborigine (Given by the Latin Word Aborigine ,,from the Beginning‘‘) Generally Means Indigenous People. - Ortner, Nathalie (Journal of A Sustainable Global South; Vol 3 No 2 (2019): August 2019, 2019)
We hope you win your battle... we know what it's like to fight for your rights.“ – Carol Barker, Aborigine (2000). By dreams we mean the belief that these beings long ago started human society - they made all natural things and put them in a special place. These dreaming beings were connected with special places or ways and paths.“ – Aborigine man (2014). We're still living in pain and trauma.“ – Yalmay Yunupingu, Aborigine (2014). If we lose this bond to the country, there will be nothing left. We will be wiped out. We exist as a people through our ancestral land. That is all we are.“ – Adrian Burragubba, Aborigine (2015). Index Terms — Aborigine, Latin, word.